Sowing legume seeds, reaping cash: a renaissance within communities in sub-Saharan Africa - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
The smallholder farmers’ access to the outputs of the breeding programs’ achievements has been very weak and hence calls for effective, more coherent, and wellarticulated design of technology and seed delivery systems of food legume crops. The Tropical Legumes projects responded to this need. This book shares impact stories and testimonies from various value chain actors who were part of the Tropical Legumes (TL) projects over the past 12 years. It presents the experiences of a diversity of actors within the grain legume value chains, with a focus on groundnut and common beans in Tanzania and Uganda, groundnut and cowpea in Nigeria, and groundnut in Ghana. All actors involved shared their feeling of being part of decade-long development project families. National agricultural research institutes, knowledge brokering organizations, NGOs, public seed companies, private seed companies, agro-dealers, individual seed entrepreneurs, farm implement makers, farmer cooperatives, farmer groups, individual farmers, women farmers, middlemen, processors, traders, and consumers were all involved in this experience. This book provides learning opportunities for development workers, technical staff, and project managers. It will also inspire development workers and project managers to share their own experiences for others to learn from.